Analisis Daya Saing Daerah Provinsi Bali Tahun 2019 - Putra, I Wayan Wiasthana Ika (Bali Membangun Bali: Jurnal Bappeda Litbang, 2019)
The Bali Province Regional Competitiveness Analysis Report 2019 presents information from various fields of development activity. This report is expected to be used as an analysis of indicators of development success that has been achieved. In addition, this report can also be used to find out the increase of development sectors and forecast future information needs. Of course this information is expected to support an increase in the implementation of development in the Bali Region.